MANAJEMEN STRATEGIS TRANSFORMASI DIGITAL: STUDI KASUS KEBERLANJUTAN EKOSISTEM PEMBELAJARAN DI SDN CIPETE 1 CURUG - Asmawi; Renita; Ryan Pratiwa Putra; Rendi Kurniawan; Atikah; Ika Pratiwi; Mutoharoh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital transformation in elementary schools often faces significant sustainability challenges, as technology adoption tends to be spur-of-the-moment and not deeply integrated into the organizational culture. This study aims to analyze digital transformation management strategies in an effort to create a sustainable learning ecosystem at SDN Cipete 1 Curug, Serang City. A qualitative approach using a case study method was used to obtain an in-depth understanding of the interaction between management policies, educator behavior, and infrastructure conditions on the ground. Data collection was conducted through triangulation, combining in-depth interviews with key informants including the principal, teachers, and school operators, as well as direct observation and documentation studies of school work plans and teaching modules. The results show that despite the school leadership's strong strategic vision, the transformation process is still hampered by the lack of formal Standard Operating Procedures (SOPs) and a significant disparity in digital competency among teachers. Furthermore, technical constraints such as slow device performance and internet network stability pose real challenges that hinder the effective integration of technology into teaching and learning activities. The study's conclusion emphasizes that the sustainability of the digital ecosystem requires synchronization between formalizing internal regulations, strengthening human resource capacity through a collaborative peer-mentoring culture, and more measurable infrastructure maintenance management. The results of this study are expected to contribute to education managers in managing digital transformation more strategically and meaningfully.